1979
DOI: 10.1111/j.1469-8137.1979.tb00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐induced Loss of Potassium From Plant Roots

Abstract: Summary The loss of K+ from excised barley, wheat, chick pea and bean roots was measured in the absence or presence of different concentrations of NaCl and mannitol. In the presence of 50 mM Ca2+, the threshhold NaCl concentration for induction of K+ loss was 160 mM for barley, wheat and chick pea and 140 mm for bean. Mannitol iso‐osmotic to 160 mM NaCl did not induce K+ loss from barley, wheat or chick pea roots indicating that the induction of K+ loss was a salt‐induced and not an osmotic injury. The prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 8 publications
3
22
1
Order By: Relevance
“…This finding was similar to that found in wheat embryos (Petruzzelli et al 1991;Cramer et al 1994). Nassery (1979) and Rehman et al (1996) reported that the toxic effect of salts in seeds is usually caused by a reduction in seed K þ concentration. Khan et al (2000) indicated that decreases in endogenous K þ levels induced by high external NaCl concentrations can be attributed to a transmembrane competition between K þ and Na þ fluxes.…”
Section: Discussionsupporting
confidence: 88%
“…This finding was similar to that found in wheat embryos (Petruzzelli et al 1991;Cramer et al 1994). Nassery (1979) and Rehman et al (1996) reported that the toxic effect of salts in seeds is usually caused by a reduction in seed K þ concentration. Khan et al (2000) indicated that decreases in endogenous K þ levels induced by high external NaCl concentrations can be attributed to a transmembrane competition between K þ and Na þ fluxes.…”
Section: Discussionsupporting
confidence: 88%
“…NaCl is the most soluble and widespread soil salt. High soil Na concentrations damage plants by causing increased tissue Na accumulation and K loss (Nassery, 1979;Greenway and Munns, 1980;Lynch and Läuchli, 1984;Zhu, 2002;Munns and Tester, 2008). Accordingly, plants have evolved a variety of salinity tolerance mechanisms, including mechanisms to restrict Na accumulation and K loss (Zhu, 2002;Smith et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1a). Upon sudden, "shock", applications of higher concentrations of Na + , membrane disintegrity due to osmotic shock and ionic displacement (particularly of Ca 2+ ), result in the release of cellular contents, including K + and water (Nassery 1975(Nassery , 1979Lynch and Läuchli 1984;Cramer et al 1985;Britto et al 2010;Coskun et al 2013; Fig. 1b), offering an alternative, or additional, explanation of enhanced K + release under Na + exposure (Britto et al 2010;Coskun et al 2013).…”
Section: Sodium Toxicitymentioning
confidence: 99%